Incentives and Timing of Prescribed Fire for Wildfire Risk Management - Jonathan Yoder; Keith Blatner (Journal of Forestry, 2004)
Prescribed fire use for wildfire fuel reduction entails trading one risk for another. Because these risks change over time as vegetation matures, prescribed fire use for wildfire risk mitigation can be viewed as a timing problem. We examine economic incentives for prescribed fire timing and use on the wildland-urban interface, the problem of heavy initial fuel loads from years of suppression and fuel accumulation, and the effect of liability, public suppression, and other factors on fuel management incentives. We conclude with a number of broad policy recommendations.